Knowledge, attitudes, and practices among patients with anemia towards disease management - Yao, Binlian; Xu, Min; Cheng, Fang; Peng, Min; Mao, Xiaopei (Frontiers in Public Health, 2024)
Objective This study aimed to assess the knowledge, attitudes and practices among anemia patients toward disease management. Methods This web-based cross-sectional study was conducted between September and December 2023 at The First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Chinese Medicine). A self-designed questionnaire was developed to collect demographic information of anemia patients, and assess their knowledge, attitudes and practices (KAP) toward disease management. Results A total of 396 valid questionnaires were collected. The mean age of the participants was 57.44 ± 16.80 years, and 52.02% were female. The mean knowledge, attitudes, and practices scores were 11.47 ± 1.73 (possible range: 0–14), 27.32 ± 2.96 (possible range: 7–35), and 40.49 ± 6.06 (possible range: 10–50), respectively. Multivariate analysis showed that bachelor’s degree or above was independently associated with sufficient knowledge (OR = 2.372, 95%CI: 1.160–4.853, p = 0.018). Knowledge (OR = 1.350, 95%CI: 1.166–1.563, p < 0.001) and hemoglobin within 60-90 g/L (OR = 1.782, 95%CI: 1.090–2.912, p = 0.021) were independently associated with positive attitudes. Moreover, attitudes (OR = 1.618, 95%CI: 1.454–1.799, p < 0.001) and diagnosis ≥1 year (OR = 1.949, 95%CI: 1.171–3.243, p = 0.010) were independently associated with proactive practices. The path analysis demonstrated that knowledge was directly and positively correlated with attitudes (β = 0.484, 95% CI: 0.363–0.647, p = 0.008), and attitudes was directly and positively correlated with practices (β = 1.195, 95% CI: 1.062–1.332, p = 0.007). Moreover, knowledge was indirectly and positively correlated with practice (β = 0.579, 95% CI: 0.434–0.805, p = 0.004). Conclusion Anemia patients have sufficient knowledge, negative attitudes, but proactive practices toward the toward disease management Comprehensive training programs are needed to improve anemia patients practices in this area.